2022
DOI: 10.3390/ijms23042130
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of miR-204 Expression during Chondrogenesis

Abstract: RUNX2 and SOX9 are two pivotal transcriptional regulators of chondrogenesis. It has been demonstrated that RUNX2 and SOX9 physically interact; RUNX2 transactivation may be inhibited by SOX9. In addition, RUNX2 exerts reciprocal inhibition on SOX9 transactivity. Epigenetic control of gene expression plays a major role in the alternative differentiation fates of stem cells; in particular, it has been reported that SOX9 can promote the expression of miRNA (miR)-204. Our aim was therefore to investigate the miR-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 42 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…differentiation. 17 Thus, by transfecting cells with anti-miR 204 we did not observe FBXW11 and RUNX2 modulation after 3 days of osteogenic differentiation (Figure 3D). However, forced expression of RUNX2 after 7 and 14 days of osteogenic differentiation, obtained by transfecting MSCs with anti-miR204, resulted in increased FBXW11 expression after 7 days (Figure 3E).…”
Section: Fbxw11 Regulates the Expression Of Runx2and Genes Associated...mentioning
confidence: 85%
See 2 more Smart Citations
“…differentiation. 17 Thus, by transfecting cells with anti-miR 204 we did not observe FBXW11 and RUNX2 modulation after 3 days of osteogenic differentiation (Figure 3D). However, forced expression of RUNX2 after 7 and 14 days of osteogenic differentiation, obtained by transfecting MSCs with anti-miR204, resulted in increased FBXW11 expression after 7 days (Figure 3E).…”
Section: Fbxw11 Regulates the Expression Of Runx2and Genes Associated...mentioning
confidence: 85%
“…16 RUNX2 can also be regulated post-transcriptionally and we recently demonstrated that RUNX2 protein levels are increased in miR-204-silenced MSCs during the middle phase of osteogenic differentiation. 17 Moreover, using melanoma cells KO for the RUNT domain of RUNX2, we demonstrated that the RUNT domain plays an important role in the modulation of the expression of genes involved in bone metastases. 18 The present work, therefore, contributes to the understanding of FBXW11 role in osteogenic cells by evaluating its modulation both during osteogenic commitment and in altered osteoblastic cells characterized by RUNX2 mutations or resulting from tumour transformation.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…miRNAs are involved in osteogenic differentiation [ 25 , 26 ]. miR-22 could induce the osteogenic differentiation of valvular interstitial cells by downregulation of CAB39 during aortic valve calcification [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…RUNX2 was highly expressed along the differentiation pathway of TSCs to hypertrophic chondrocytes and TSCs to osteoblasts. SOX9 was reported to be a pivotal transcriptional regulator of chondrogenesis 22 . MMP13 was related to the osteogenesis 23 .…”
Section: Discussionmentioning
confidence: 99%